MENGEMBANGKAN BAKAT DAN KREATIVITAS UNTUK BERKARYA DAN BERWIRAUSAHA DI PKBM BUDI UTAMA CIAMIS - Dini Tresna Asih; Ainan Salsabila; Imtyaz Nazifa Ainuurafiq; Haura Salsabila; Rizal Ramadhan; Lilis Karwati (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2023)
Empowerment, the community in entrepreneurship education and skills in the field of catering can support food self-sufficiency in the community in the LPK Gemilang area in Pacasila Lengkongsari, Tasikmalaya City which previously had not shown any efforts to increase family income, let alone lead to community welfare and Entrepreneurial Skills in the economic field towards food self-sufficiency. This encourages the study of community empowerment through entrepreneurial skills education programs (PKW) and skills in the bakery sector in increasing income at LPK Gemilang, Tasikmalaya City. Based on these problems, this study is for empowerment through an entrepreneurial skills education program (PKW) and skills in the bakery sector in increasing income. This study was conducted on community groups with our aim in this service to provide education about the knowledge, skills and skills of citizens, as well as income generation and the sustainability of women's empowerment programs as indicated by the existence of product development and the formation of team independence. In business activities to increase income as an effort to meet needs, and to change people's behavior and attitudes in a positive direction, the conclusion shows that community empowerment through entrepreneurial skills education programs (PKW) and skills in the bakery sector supports income, community income in the business sector.